IMPROVING THE COMPETITIVENESS OF MEDICAL SERVICE PROVIDERS SMALL BUSINESSES (Marketing Journal, 2025)
This article focuses on improving the assessment of competitiveness for medical service providers based on methods that utilize marketing mix characteristics and the medical service environment.
Keywords: medical services; competitiveness of medical services; marketing mix; medical service environment; service portfolio; competitiveness polygon; competitiveness index